Critical Multilingual Literacy Awareness (CMLA) as a Catalyst for Developing Students' Critical Thinking Literacy in Literature - Hizkia Silaban; Salsabila Nur Fadilah Sayuti; Rita Hartati (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This article explores the impact of Critical Multilingual Literacy Awareness (CMLA) on enhancing critical thinking skills among literature students. By integrating multilingual texts with critical literacy practices, CMLA fosters a more nuanced approach to literary analysis, encouraging students to engage deeply with diverse linguistic and cultural perspectives. The study employs a qualitative case study methodology, involving 30 undergraduate literature students from varied linguistic backgrounds, and utilizes classroom observations, interviews, and written assignments to assess outcomes. Findings reveal significant improvements in students' abilities to conduct comparative analyses, understand contextual nuances, and engage in reflexive thinking. The results underscore the transformative potential of CMLA in literature education, advocating for its broader implementation to cultivate critical thinking and intercultural competence in an increasingly interconnected world. This research not only contributes to the academic discourse on multilingualism in education but also provides practical strategies for educators seeking to enrich their teaching practices.